2014
DOI: 10.3928/1081597x-20140320-04
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. Army Surface Ablation Study: Comparison of PRK, MMC-PRK, and LASEK in Moderate to High Myopia

Abstract: MMC-PRK showed some benefits in minimizing corneal haze formation. One year after surgery, there was no discernible difference in the postoperative refractive outcomes among the three methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 29 publications
2
40
1
Order By: Relevance
“…This eye was still highly myopic after the surgery (−8.00 D) and had not developed haze. Significant haze 6 weeks after surgery was not found in any cPRK eyes, but in 16 % of LASEK eyes, which is similar to other cPRK and LASEK findings [13,25,27]. Significant haze following cPRK has been reported, but only in studies using old generation excimer lasers [11,16].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This eye was still highly myopic after the surgery (−8.00 D) and had not developed haze. Significant haze 6 weeks after surgery was not found in any cPRK eyes, but in 16 % of LASEK eyes, which is similar to other cPRK and LASEK findings [13,25,27]. Significant haze following cPRK has been reported, but only in studies using old generation excimer lasers [11,16].…”
Section: Discussionsupporting
confidence: 67%
“…Disadvantages of surface ablation techniques include a relatively long visual recovery period, postoperative pain, and higher risk of corneal haze and myopic regression as compared to intrastromal techniques, especially when treating high degrees of myopia [2,5,6,8,9]. Technological advancements with larger optical zones, corneal cooling, epithelial repositioning, mitomycin C, and highfrequency flying-spot excimer lasers with eye-trackers have improved outcomes and reduced the risk of complications after surface ablation techniques [3,7,[10][11][12][13][14][15][16]. The umbrella term for many of these improvements is "advanced surface ablation," which includes photorefractive keratectomy with cooling (cPRK) and laser-assisted subepithelial keratectomy (LASEK), among others [17].…”
Section: Introductionmentioning
confidence: 99%
“…One year after surgery, there was no discernible difference in the postoperative refractive outcomes among the three methods. 28 Similarly, a prospective randomised controlled study showed MMC may not be needed to prevent haze after modern PRK with a four-month steroid taper. There was no clinically significant difference in haze formation between MMC eyes and control eyes at the concentration and exposures used.…”
Section: Mitomycin Cmentioning
confidence: 99%
“…35 Since then, it has been realised in randomised studies that the technique is not superior to conventional PRK in terms of patient comfort, reduction of haze or regression. 28 It seems that the manipulation of the epithelium would leave non-surviving cell and that the biological barrier of the replaced epithelial cells is insufficient to reduce a wound-healing response.…”
Section: Laser Subepithelial Keratomileusismentioning
confidence: 99%
“…Some prefer PRK because of the risk of post-LASIK ectasia, and some prefer phakic intraocular lens (PIOL) implantation due to the risk of corneal haze after PRK. [1][2][3] We designed a matched comparative study of patients with 48.0 diopters (D) of myopia and compared results of treatment with PRK and PIOL in these two groups. Our 1-year results 4 indicated that surface ablation and PIOL implantation correct uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), refraction, and astigmatism similarly, and they do not impact mesopic contrast sensitivity (CS).…”
Section: Introductionmentioning
confidence: 99%